2010
DOI: 10.1103/physreve.81.061121
|View full text |Cite
|
Sign up to set email alerts
|

Phase coexistence in consolidating porous media

Abstract: The appearance of the fluid-rich phase in saturated porous media under the effect of an external pressure is investigated. For this purpose we introduce a two field second gradient model allowing the complete description of the phenomenon. We study the coexistence profile between poor and rich fluid phases and we show that for a suitable choice of the parameters nonmonotonic interfaces show up at coexistence.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 18 publications
0
50
0
Order By: Relevance
“…In the papers [8,9] we have studied the stationary version of the problem (2.25) corresponding to the potential energies (2.24) and (6.1) to describe the possible occurance of an interface between two phases differing in fluid content. In fact this model is built in such a way to describe the existence of two states of equilibrium: the fluid-poor phase (ε s , m s ) and the fluid-rich phase (ε f , m f ) corresponding to the two minima of the double-well potential energy Ψ in (6.1).…”
Section: Negativity and Boundedness Of The Strain And Density: Proof mentioning
confidence: 99%
See 2 more Smart Citations
“…In the papers [8,9] we have studied the stationary version of the problem (2.25) corresponding to the potential energies (2.24) and (6.1) to describe the possible occurance of an interface between two phases differing in fluid content. In fact this model is built in such a way to describe the existence of two states of equilibrium: the fluid-poor phase (ε s , m s ) and the fluid-rich phase (ε f , m f ) corresponding to the two minima of the double-well potential energy Ψ in (6.1).…”
Section: Negativity and Boundedness Of The Strain And Density: Proof mentioning
confidence: 99%
“…In particular, for both figures 6.1-6.2 in the top row we used as initial guess a costant function equal to the fluid-poorphase, while in the central row it has been used a costant function equal to the fluid-rich-phase. Finally, in the bottom row we used as intial guess the solution to the same stationary problem with Dirichlet boundary conditions fixing the two phases at the ends of the sample, namely, (ε(0), m(0)) = (ε s , m s ) and (ε(1), m(1)) = (ε f , m f ) (see [8]).…”
Section: Negativity and Boundedness Of The Strain And Density: Proof mentioning
confidence: 99%
See 1 more Smart Citation
“…In the model which is going to be presented in this paper, on the other hand, the behavior of the solid skeleton is described by means of a strain gradient model, to predict localized strains and fracture, when considering irreversible processes. To the best of author's knowledge, no general model accounting for both the above mentioned items, say localization in fluid flow and strain, can be retrieved from the literature, except a preliminary study by the author [87], stemming from previous results on modeling of porous media saturated by quasi-incompressible fluids, see [42,88,89] and [21,22,23,24,25]. Within this enhanced framework, the hydro-mechanical coupling is therefore responsible not only for the effects of average variations of the hydraulic regime within the RVE on the skeleton deformation, and vice-versa, see among others [78,3,95,19,83,84], but it can also account for the effects of capillary fingering on damaging and fracturing of the skeleton and vice-versa for the effects of strain localization on permeability variations and heterogeneous/anisotropic fluid flow.…”
Section: Introductionmentioning
confidence: 99%
“…In this theory two order parameters m and ε are introduced, having respectively the physical meaning of fluid density and solid strain. In [3,7] the interface separating the two coexisting phase has been studied and it has been shown that its localization properties, due to the asymmetry of the potential energy, are not trivial.…”
Section: Introductionmentioning
confidence: 99%